More Academic Librarians in Arkansas with Faculty Status and Rights but Decreased Benefits and Increased Responsibility - Lê, Mê-Linh (Evidence Based Library and Information Practice, 2013)
A Review of: Vix, H. M., & Buckman, K. M. (2011). Academic librarians: Status, privileges, and rights. Journal of Academic Librarianship, 38(1), 20-25. doi: 10.1016/j.acalib.2011.11.004 Objective – To provide cross-comparable information on the number of students per librarian, salary, faculty status, contract lengths, and maternity benefits of academic librarians. Design – Online questionnaire. Setting – Four-year private, four-year public, and two-year public academic institutions in Arkansas. Subjects – Academic library deans and directors were surveyed three times over a six-year period. Methods – Three surveys were sent to library deans and directors of four-year private, four-year public, and two-year public academic institutions in Arkansas in 2007, 2009, and 2011. The surveys were created by the College and University Library Division of the Arkansas Library Association, with questions created based on reports from the Association of College and Research Libraries (e.g., Standards and Statements). Committee members tested the survey before distribution. Over the course of the six-year period the questions were modified and were chosen to ensure that respondents could easily answer them (i.e., no questions on topics such as retirements, vacation, which can vary significantly from librarian to librarian). All responses were confidential. Main Results – The 2007 survey had a 78% response rate (n=35/45); the 2009 survey had a 93% response rate (n=42/45); and the 2011 survey had a 90% response rate (n=44/49). While the survey covered a number of topics (shown in supplementary material online), the article focused on five areas of interests and had the following findings. 1) The number of students per librarian is increasing at four-year private and two-year public institutions. While the data shows a decrease in the ratio at four-year public institutions the authors believe this is due to the addition of new institutions in the follow-up surveys, one of which had a very low study-to-librarian ration. 2) Tenured librarians make more than non-tenured librarians. 3) The number of institutions granting faculty status is increasing at a statistically significant rate at four-year private and two-year public institutions, and has remained relatively constant at four-year public institutions. 4) Most libraries have 12-month contracts for librarians, although this has decreased slightly over the survey period. 5) The number of institutions providing paid maternity leave has decreased. Conclusion – This study provides a broad overview of the changing state of academic librarians’ rights and benefits in Arkansas over the last six years. Some of the trends demonstrated, such as an increase in the number of students per librarian, are potentially troubling and may have a negative impact on the quality of service provided by individual institutions. Other trends, such as increases in institutions granting faculty status to librarians and decreasing the number of 12-month contracts, may signal that some institutions are beginning to acknowledge the significance and impact of librarian research. Ultimately, this article provides a starting point for other states and provinces to begin collecting similar data in an attempt to understand changing trends in academic libraries.